Surface Restructuring Prussian Blue Analog-derived Bimetallic CoFe Phosphides by N-doped Graphene Quantum Dots for Electroactive Hydrogen Evolving Catalyst - Lin, Wei-Shiang; Rinawati, Mia; Huang, Wei-Hsiang; Chang, Chia-Yu; Chang, Ling-Yu; Cheng, Yao-Sheng; Chang, Ching-Cheng; Chen, Jeng-Lung; Su, Wei-Nien; Yeh, Min-Hsin (Journal of colloid and interface science, 2024)
[Display omitted] •A novel PBA-derived CoFe phosphides has been developed for hydrogen evolution reaction.•The catalytic activity of the PBA-derived phosphides has been significantly enhanced by NGQD.•The role of NGQD in inducing surface restructuring of the CoFeP has been investigated by XAS.•The surface-restructuring NGQD/CoFeP exhibit remarkable HER activity and stability. As a crucial stage of electrochemical water splitting, hydrogen evolution reaction (HER) favour catalyst to attain rapid kinetics for its broader application, alternating platinum in the acidic environment. Transition metal phosphides (TMPs) are one kind of earth-abundant, nonprecious-based catalyst which has been classified as a viable alternative and active for HER. While the performance remains inferior to Pt which primarily targets durability under high current density, pinpointing the reconfiguration strategy would be critical to their catalytic competency. Herein, we reported engineered N-doped graphene quantum dots (NGQD) on the surface of bimetallic CoFe phosphide (CoFeP) derived from bimetallic cobalt iron Prussian blue analogue (CoFePBA) as an efficient HER. By introducing the NGQD, the surface architect and electronic state of the transition metal are altered through an adjusted electronic configuration and thus, improving the electrocatalytic activity. The X-ray absorption spectroscopy (XAS) highlighting the role of NGQD, which successfully induced the electron density of Co atoms, further expedites its conductivity and electroactivity. The optimized NGQD/CoFeP substantially surpasses an overpotential of 70 mV (vs. RHE) at the current density of 10 mA cm-2 in 0.5M H2SO4. Furthermore, the NGQD/CoFeP maintains its exceptional stability under an extremely high current density of 600 mA cm-2 after 12 hours of continuous operation. Our findings show that NGQD/CoFeP might demonstrate as a viable alternative to the conventional Pt electrocatalyst in commercial water splitting for hydrogen generation.